2011
DOI: 10.1073/pnas.1113002109
|View full text |Cite|
|
Sign up to set email alerts
|

Specific neural substrate linking respiration to locomotion

Abstract: PERSPECTIVECorrection for "The role of terrestrially derived organic carbon in the coastal ocean: A changing paradigm and the priming effect,"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 55 publications
5
65
0
Order By: Relevance
“…Chemical stimulation of the PT with local microinjections of 3.0 to 8.0 pmol of D-glutamate (5 mM, 17-43 pulses of 20 ms, 0.6-1.6 nL per microinjection) into the site used for electrical stimulation, was confirmed to elicit locomotion and reticulospinal discharges in one preparation. This is consistent with previous observations that electrical or chemical stimulation with D-glutamate of this region initiates locomotion (10,11). By using targeted whole-cell patch clamp recordings in an isolated brain preparation (Materials and Methods), we found that trains of stimuli (10-s train, 4-5 Hz, 10-35 μA, 2-ms pulses) to the PT (Fig.…”
Section: Significancesupporting
confidence: 77%
See 1 more Smart Citation
“…Chemical stimulation of the PT with local microinjections of 3.0 to 8.0 pmol of D-glutamate (5 mM, 17-43 pulses of 20 ms, 0.6-1.6 nL per microinjection) into the site used for electrical stimulation, was confirmed to elicit locomotion and reticulospinal discharges in one preparation. This is consistent with previous observations that electrical or chemical stimulation with D-glutamate of this region initiates locomotion (10,11). By using targeted whole-cell patch clamp recordings in an isolated brain preparation (Materials and Methods), we found that trains of stimuli (10-s train, 4-5 Hz, 10-35 μA, 2-ms pulses) to the PT (Fig.…”
Section: Significancesupporting
confidence: 77%
“…Locomotor movements of body were recorded (30 frames per second) by a video camera (HDR-XR200; Sony) positioned 1 m above the recording chamber. Locomotor movements were tracked and analyzed by using custom written scripts in Matlab (MathWorks) previously used in our laboratory (11,35). Briefly, tracking markers were equidistantly distributed along the midline of the body by using geometrical analysis of the body.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure was similar to that previously used in lampreys (22,57,58) and salamanders (7). Biocytin (Sigma-Aldrich B-4261) and TRDA (Molecular Probes D-3328) were used for retrograde tracing.…”
Section: Methodsmentioning
confidence: 99%
“…Afferent input to the investigated regions may also arise from structures within the central nervous system that are known to influence the respiratory activity, such as the neural system that is involved in triggering both locomotion and increases in respiratory activity in response to internal cues in specific behavioral contexts, such as exploration, food seeking, reproduction and defense reaction. These mechanisms rely on supraspinal structures and involve neurons of the mesencephalic locomotor region (Garie´py et al, 2010(Garie´py et al, , 2012b. We cannot exclude that components of this neural system may operate by removing an inhibitory control on both the respiratory motoneuron region and the OLA.…”
Section: Functional Considerationsmentioning
confidence: 99%